2015
DOI: 10.1016/j.ecolind.2015.05.063
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seasonality, fish size and reproductive status on EROD activity in Plagioscion squamosissimus: Implications for biomonitoring of tropical/subtropical reservoirs

Abstract: a b s t r a c tEthoxyresorufin-O-deethylase (EROD) activity is considered an important biomarker for aquatic environmental contamination. Although EROD activity has been widely used as a biomarker of exposure to polycyclic aromatic hydrocarbons in fish, this activity can be influenced in the field by spatial-, seasonalor individual-related factors. We therefore performed a comparative study of hepatic EROD activity levels in the croaker Plagioscion squamosissimus to determine whether variations existed in enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Consequently, this effect is more pronounced during breeding periods. This effect has been reported by some authors (Wunderlich et al, 2015). Another possibility for EROD inhibition in some fish species is the presence of trace metals, as demonstrated in some studies (Roméo et al, 1994;Guilherme et al, 2008;Vieira et al, 2009).…”
Section: Biotransformation Enzymessupporting
confidence: 74%
“…Consequently, this effect is more pronounced during breeding periods. This effect has been reported by some authors (Wunderlich et al, 2015). Another possibility for EROD inhibition in some fish species is the presence of trace metals, as demonstrated in some studies (Roméo et al, 1994;Guilherme et al, 2008;Vieira et al, 2009).…”
Section: Biotransformation Enzymessupporting
confidence: 74%
“…Furthermore, concentrations of Pb in samples from the port of Genoa were substantial when compared to other studies on Mugilidae fish, where a higher content of Pb is reported in gills, reaching a maximum of 3 mg/kg, while Pb concentrations in the liver and muscle usually do not exceed the values of 1 mg/kg and 0.3 mg/kg, respectively (Bat et al 2018 ; Engin 2015 ; Licata et al 2003 ; Rajeshkumar et al 2015 ; Salem and Ayadi 2016 ; Stancheva et al 2013 ; Usero et al 2003 ). Another aspect that was investigated, concerning the concentration of metals found in the tissues, was the possible influence of size on the comparison between sites; in fact, since the fish from the port were bigger, and therefore presumably older, than those from the fishpond, they might show higher values of metals due to prolonged exposure (Wunderlich et al 2015 ). This hypothesis was refuted by the statistical analysis that tested the correlation, using Kendall’s tau, between size (length/weight) of individuals and concentration of metals in different tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The species has a wide feeding spectrum (Hahn et al 1999;Bennemann et al 2000;Bennemann et al 2006;Santos et al 2016), although it is mostly piscivorous (Hahn et al 1997) or a generalist carnivore (Bennemann et al 2011;Rocha et al 2015;Neves et al 2015). Due to its wide geographical distribution in the Amazon, abundance and tolerance to environmental stress in dammed river systems, and the relevance of studyng species on the top of the aquatic food chain (Custódio et al 2020), total mercury analysis of P. squamosissimus can help reveal important environmental features in tropical aquatic environments (Wunderlich et al 2015).…”
Section: Introductionmentioning
confidence: 99%